Islamic Educational Literature and the Methodology of Takhrij Hadith: Concept, History, and Practice of Systematic Tracing of Sanad-Matan - Nur Asiah; Zainal Arif (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
The widespread practice of quoting hadith without clear sanad and quality poses a significant risk of religious disinformation, necessitating the systematization of an integrated takhrij methodology. This study aims to analyze the historical conceptualization, methodological reconstruction, and practical implementation of hadith takhrij as a scientific verification mechanism. Using library research methods with a qualitative descriptive-analytical approach to classical books (such as Al-Mu'jam al-Mufahras and Musnad Ahmad) and contemporary literature, this study identifies five systematic methods: (1) based on the matan wording, (2) the first wording, (3) the first narrator, (4) thematic, and (5) quality classification. Significant novelty lies in the reconstruction of comprehensive operational procedures starting from keyword identification, i'tibar sanad analysis, to jarh wa ta'dil evaluation that integrates the disciplines of rijal. Unlike previous studies, which were limited to descriptive normative research, this study offers an applicable methodological map by emphasizing the urgency of using hadith dictionaries, the poles of the sittah, and biographies of narrators to maintain the authenticity of Islamic scholarly tradition. The impact of this research is vital for the academic standardization of hadith citation and the prevention of the spread of fabricated hadith in the digital era. The conclusion suggests that mastery of the takhrij methodology is an essential prerequisite for the validity of the sanad-matan in the development of contemporary Islamic studies.